Penerapan Undang Undang Nomor 13 Tahun 2003 Pada Sistem Upah Di Indonesia - Ni Putu Decy Arwini (Jurnal Ilmiah Vastuwidya, 2020)
Wage, is the most important reason for the employee to do their job activity. Even this is not a reson for every worker but it’s still a biggest reason. Generally, there is 3 party that is involve in wage system in Indonesia. There is a company, worker n the government. Company is a business enitity own by individual or group that employ people and give a wage in return. Employ is a person who can do a job to produce a product or services to fulfil their needed. Government as a regulator dan consultant when this two party on their activityThere is many wage system in our country, depend on company size, economic condition, etc. ths system such as wage system based on output, wage system based on time, wholesale system, wage system based on bonus and business partner wage system. In wage calculation, company must consider about minimum regional wage. Besaide that, they also must calculate about overtime work. In Indonesia, overtime work calculate every hour and it’s depend on 5 or 6 day work day in a week. Basically, wage must be worth for humanity and balanced with workers sacrifice for the company.